[Mn(co)(3)(bpy)(n-2-chlorobenzylbenzimidazole)] otf complex as a new photoactivatable co-releasing molecule - Ustun, E.; Dusunceli, S. Demir; Ozdemir, I. (Bulgarıan acad scıence, central lıbrary 7 noemvrı no 1, sofıa, 00000, bulgarıa, 2017)
Metal carbonyl complexes have been accepted major for storage and transportation of carbon monoxide which is an important gasotransmitter. We synthesized novel manganese(I) carbonyl complex with general formula [Mn(CO)(3)(bpy)L] OTf (bpy = 2,2'-bipyridyl, L= N-(2-chlorobenzyl) benzimidazole, OTf = SO3CF3). The complex was characterized by LC-MS, H-1 NMR, 2D-COSY NMR, C-13 NMR, IR and elemental analysis. The CO-releasing properties of the complex were investigated. The DFT/TDDFT analyses were also made by ORCA package program.